2017
DOI: 10.1021/acs.energyfuels.7b02428
|View full text |Cite
|
Sign up to set email alerts
|

N2O Formation Characteristics in Dielectric Barrier Discharge Reactor for Environmental Application: Effect of Operating Parameters

Abstract: The present study is devoted to the investigation of N2O formation characteristics in dielectric barrier discharge (DBD) reactor for environmental application. The effect of operating parameters, such as specific energy density (SED), O2 concentration, NO initial concentration, and residence time on N2O concentration was investigated in dry O2/N2 mixtures. N2O formation from bulk gas (O2 and N2) is inevitable in DBD chemical process and was observed in all DBD reactors. N2O concentration shows an exponential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…investigated the importance of back‐reaction on NO oxidation and proposed that the presence of reaction (4) can lead the product NO 2 back to NO. The reaction (5) between plasma species can also produce undesired by‐products such as N 2 O O+normalNO2NO+normalO2 normalO2+normalN2normalA3u+normalN2O+O …”
Section: Introductionmentioning
confidence: 99%
“…investigated the importance of back‐reaction on NO oxidation and proposed that the presence of reaction (4) can lead the product NO 2 back to NO. The reaction (5) between plasma species can also produce undesired by‐products such as N 2 O O+normalNO2NO+normalO2 normalO2+normalN2normalA3u+normalN2O+O …”
Section: Introductionmentioning
confidence: 99%
“…Guaitella et al conducted af urther study on the surface absorption of plasma-treated Pyrex and pointed out that the main pathway converting the absorbed nitrogen speciest oN O x was the reaction between the surface-absorbed oxygen atoms through the Eley-Rideal (ER) mechanism, [54] which described the reaction between absorbeda nd gas-phase molecules. [17,55,58] Al ater study conductedb yT ang et al [59] also investigated plasma-based NO x synthesis using metal-oxide catalysts, which was worth comparing with Patil et al [55] because both studies examined the plasma-based NO x synthesis for as pecific energy inputr ange between 1300 and 1800 JL À1 .R esults from Patil [59] These two studies also investigated the effect of the plasma-discharge parameters, the results of which provided understanding of the potential plasma influence on the characterization of catalyst surfaces. [56,57] Within these studies, the paper for DBD plasma indicated that high surface area was as ignificant factor that could contributet ot he surface catalytic activity.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
“…Patil et al studied the catalytic synthesis of NO x using metal-oxide catalysts for both DBD [55] and glidinga rc plasmas. [57,59] Another aspect of the synergyb etween catalyst and plasma is the influence of plasma on the catalyst. [55] Interestingly,t he authors also concluded that the gas-phaser eactions between the excited nitrogen and oxygen species were still dominante ven though the chances of vibrational-plasma-excited nitrogen atoms reactingw ith surface-absorbed oxygen atoms were highera fter increasing the catalystl oadinga nd surfacea rea.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
See 2 more Smart Citations